Effectiveness Test Of The Inhibition Power Of Ethanol Extract Of Salak Pondoh Fruit Skin (Salacca Zalacca (Gaertn.) Voss) Against Eschericia Coli Bacteria And Salmonella Typhi Bacteria - Manahan Situmorang; Widya Fitri; Julia Susanti; Enjelina Br Sembiring Kembaren (Journal of Innovative and Creativity, 2025)
Diarrhea is the occurrence of defecation with a more liquid consistency than usual and may be accompanied by liquid mucus or blood with a frequency of three times or more within 24 hours. Salak pondoh contains chemical compounds consisting of flavonoids, saponins, phenols, tannins, alkaloids, chlorogenic acid, ferulic acid, and protocatechuic acid. The bacteria Escherichia coli and Salmonella typhi cause diarrhea and fever due to tissue damage. Based on the above description, this study will test the effectiveness of the inhibitory power of the ethanol extract of salak pondoh fruit skin (Salacca zalacca (Gaertn.) Voss) against Escherichia coli and Salmonella typhi bacteria. This research method uses an experimental agar diffusion method to test the antibacterial activity of salak pondoh fruit skin with concentrations of 20%, 40%, 60%, and 80%. The results of this study show that the concentrations of 20%, 40%, 60%, and 80%, and the positive control (chloramphenicol) of salak pondoh fruit skin have antibacterial inhibitory power against the growth of Escherichia coli bacteria, as indicated by inhibition diameters of 4.81 ± 22.74 mm, 7.81 ± 22.74 mm, 10.15 ± 06.65 mm, 15.07 ± 19.00 mm, and 27.56 ± 48.58 mm, respectively. For Salmonella typhi, the antibacterial inhibitory power was 2.22 ± 18.19 mm, 3.48 ± 23.30 mm, 7.32 ± 67.41 mm, 11.68 ± 112.07 mm, and 24.14 ± 77.77 mm, respectively. The conclusion from the results of this study is that the effectiveness test of the ethanol extract of salak pondoh fruit skin (Salacca zalacca (Gaertn.) Voss) can inhibit the growth of Escherichia coli and Salmonella typhi bacteria, and the concentration that can significantly affect bacterial growth inhibition is 80%.